Correlation between inflammatory infiltrate and epithelial lining in 214 cases of periapical cysts - Barbara Albertini Roquim Alcantara; Marina Lara de Carli; Luiz Alberto Beijo; Alessandro Antonio Costa Pereira; Joao Adolfo Costa Hanemann (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The aim of this study was to evaluate the prevalence of periapical cysts, identify their clinical and microscopic features and correlate their microscopic features with the inflammatory infiltrate present in the lesion site. A total of 214 cases were collected over a 10-year period. Clinical data, including gender, age, race, symptoms and location of the lesion, were recorded. Two independent examiners with no prior knowledge of the patients' clinical data conducted the microscopic evaluations. Statistical analyses were performed using Fisher's or chi-square tests at a 5% level of significance. The results showed that periapical cysts were more prevalent in white women, with a mean age of 35 years, and in the anterosuperior region. The majority of the lesions were lined by atrophic cystic epithelium, which was associated with moderate inflammatory infiltrate in the cystic capsule (p < 0.01), with a diffuse localization pattern (p = 0.03) and absence of neutrophils (p = 0.01). Our findings suggest that periapical cysts lined by atrophic epithelium are related to the presence of moderate mononuclear inflammatory infiltrate.